The Effect of Premarriage Skills Training on Communication Skills and Problem Solving in martyr and Veteran girls in Guilan province - M. Khosrojavid; A. Aslipoor; M. Firoozshad; R. Hedaiatsafa (Afarand Scholarly Publishing Institute, 2015)
Aims: Most of the marital problems are due to lack of any communication or problem-solving skill. Based on the conducted studies, teaching such skills, before marriage, leads to less conflicts and higher marital satisfaction. The aim of this study was to investigate the effectiveness of teaching the pre-marriage skills on the communication and problem-solving skills in the daughters of the martyrs and veterans of Gilan Province.  Materials & Methods: In this semi-experimental pretest-posttest study with a control group, 18-25 years old daughters of martyrs and veterans of the cities of Gilan Province were studied in 2014. 50 persons (from Rasht) and 30 persons (from Lahidjan) were randomly selected via Multi-step Cluster Method. The persons were randomly divided into two groups including control and experimental. Ten 90-minute pre-marriage skills training sessions were conducted in experimental group (one session per week). Communication Skills Questionnaire and Problem-solving Scale were completed by the groups at the pretest and posttest stages. Data was analyzed using one-variable and multivariate covariance analysis methods.   Findings: At the posttest stage, there were increases in the mean scores of the communication skills of experimental group in all the sub-scales including emotion management, understanding other persons, and assertiveness (p<0.001). In the problem-solving scale, the scores of experimental group decreased in distress, avoidance, and controlling subscales, while there were increases in the scores of creativity, trust, and turning subscales (p<0.001).  Conclusion: It is very important to teach the communication and problem-solving skills to young persons and especially, the daughters of the martyrs and veterans before marriage to enhance the marriage quality and reduce the conflicts.